IMPLEMENTASI PERWAKO SOLOK NO 6 TAHUN 2015 TENTANG SISTEM PROSEDUR PENEMPATAN PEDAGANG PASAR SEMI MODERN - Reza Fajriandi; Afriva Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This research to purpose to find out how to implementation of Solok Mayor Regulation No. 6 in 2015 concerning the System and Procedure of Merchant Posting in Solok Semi Modern Market. This research was carried out because it saw trade activities in the Semi Modern Market in Solok City which was very quiet. This research is a qualitative method research with a descriptive approach. The informants selected in this study used purposive sampling and incidental sampling techniques. The technique of collecting data is through observation, documentation, and in-depth interviews. As well as testing the validity of the data using source triangulation and method triangulation. Based on the results of this research indicate that in the implementation of the policy of Mayor Solok Regulation No. 6 in 2015 concerning the System and Procedure of Placement of Traders in the Semi-Modern Market in Solok City is still not well implemented. It was seen from the trading activities in Solok City Semi Modern Market which are still lonely due to the reluctance of traders to open their wares for fear of losing customers and decreasing income.